Construção e validação do instrumento para consulta de enfermagem ao indivíduo com diabetes mellitus tipo 2 - Pimentel, Thiago Souza (2018)
Methodological study, whose objective was to bluid validate the content and appearance of a new version of the instrument for Nursing Consultation in Basic Care for individuals with diabetes mellitus type 2 in Basic Care. The study had as a theoretical framework the Theory of Praxis for Intervention in Collective Health (TPICH) by Emiko Egry. The methodological procedure was based on Pascali's theoretical pole of the psychometric model (2010). In this study of the instrument was developed using the International Classification for Nursing Practice - CIPE® Version 2015. This new version was applied in 21 people with diabetes mellitus type 2 who were registered in a Family Health Unit, in the municipality of Aracaju, in Sergipe; this action constituted the pretest phase. At the end of this stage, the instrument with 122 items went down to 99 items, which were submitted to a panel of eleven judges to validate their content and appearance. Using a Likert scale of three points, the judges evaluated each item regarding their permanence in the instrument; they also judged on the psychometric criteria of: objectivity, clarity, precision, typicality, simplicity, relevance, modality and credibility. Subsequently, the Content Validity Index of each of the items (CVI) was calculated. The categorical data were described by means of simple frequencies and percentages and the continuous or discrete data with average and standard deviation. In this study, the content validity of the items was considered when CVI ≥ 0.80, this according to the methodological referential. The results showed that eight items (local of work protected, police service, insomnia, self-perception, psychological condition, eye disturbances, cut nails and foot with blisters) obtained CVI ˂0.80; the first six items were removed from the instrument, while the last two items remained subitems due to the importance of their assessments in individuals with diabetes mellitus type 2. All other items stayed as they were or with the alterations suggested by the specialists. In validating the appearance, 100% of the judges approved the instrument to collect the data in individuals with diabetes mellitus type 2. The suggestions of the judges were accepted in their majority; therefore, a new evaluation was not necessary. To guide the evaluation actions of nurses, in a homogeneous and unequivocal way, it was written an appropriate instruction guide. In this way, it was found that this new version of the instrument has validity of content and appearance. In order to have a technology that can be reproduced in various nursing services of Basic Care with this we will contribute to the organization of the work process of nurses, granting them autonomy and visibility in their practice.